PERSONAL QUALITIES OF BRILLIANT SURGEONS: A MYTH OR REALITY: Personal Qualities of Brilliant Surgeons - Khan, Haroon Sabir; Khan, Rehan Ahmed; Azhar, Joharia (Pakistan Armed Forces Medical Journal, 2018)
Objective: To explore the qualities of brilliant surgeons that makes them distinctive.Study Design: A qualitative exploratory study.Place and Duration of Study: The study was conducted in Armed Forces Hospitals, Rawalpindi, from Jan to Jul2017.Material and Methods: A purposive sampling technique was applied for in-depth, semi-structured interviews of19 members (ten surgeons, six anesthesiologists and three operation room assistants) having experience ofsurgical environment for more than 20 years in different institutions. Computer Assisted Qualitative DataAnalysis Software (CAQDAS) was employed for thematic data analysis using software NVIVO 11 Pro.Results: Study participants reported observation of distinctive personality characteristics of a few surgeonshitherto termed as “brilliant”. Multifaceted aspects of their personality were identified and categorized into fivemajor themes: mental, psychological and emotional, social, mechanical, and structural strength. The first threethemes were found to be common among brilliant achievers in all other professions as well, however, themechanical and structural strength domains were considered to have unique and substantial bearing on theachievement of brilliance in surgery.Conclusion: A category amongst the surgeon has been identified and termed as “brilliant”. These brilliantsurgeons were gifted in five domains of their personality with a distinct set of qualities which made them outclasstheir contemporaries.